Teologi Transformatif: Eksplorasi Pandangan Paulus tentang Keselamatan dan Penebusan dalam Perjanjian Baru (International Forum of Researchers and Lecturers, 2025)
This study investigates Paul's theological views regarding the concepts of salvation and redemption in the context of the New Testament. The primary focus is an exploration of the transformative theology underlying Paul's teachings and its impact on Christian spiritual beliefs and practices. Through analysis of Paul's writings, this research aims to open a deeper understanding of how Paul's concepts of salvation and redemption provide the basis for inner and moral change.